The Citizenship Paradigm Debate in Dual Citizenship Discourses in Indonesia - Ramdhani, Hilal (Research and Development Agency Ministry of Home Affairs, 2022)
Various adjustments regarding citizenship law regulations in Indonesia still do not provide accommodation for all citizens. After the enactment of Law Number 12 of 2006 concerning Citizenship, there was pressure from the Indonesian diaspora to implement dual citizenship. This urge received a rejection from other citizens because it endangered security, economy, politics and questioned loyalty as a citizen. This study aims to examine in the literature the differences in paradigms of globalist and nationalist groups in Indonesia and the reality that occurs in other countries regarding dual citizenship. The study uses a qualitative approach with a literature study to examine the issue of dual citizenship in Indonesia and compare the development of dual citizenship in other countries. The results showed that the debate on the dual citizenship paradigm is in the material and immaterial debates. The group that supports dual citizenship wants distributive justice in terms of material (economics) for those who live abroad. In contrast, the opposing group wants to maintain immaterial aspects. (identity, culture, and ideology). This situation makes Indonesia unable to fully implement dual citizenship. Besides that, Law Number 12 of 2006 concerning citizenship at the beginning of its formation was intended to preventÂ apatrideÂ andÂ bipatride. On this basis, recommendations for stakeholders related to dual citizenship need to be careful in making policies, being able to accommodate the various wishes of citizens, as well as further reviewing the legal and social impacts caused when implementing dual citizenship in Indonesia.